The evolution of begging: Signaling and sibling competition - Rodríguez-Gironés, Miguel A. (The National Academy of Sciences of the USA, 1996)
In many species, young solicit food from their parents, which respond by feeding them. Because of the difference in genetic make-up between parents and their offspring and the consequent conflict, this interaction is often studied as a paradigm for the evolution of communication. Existent theoretical models demonstrate that chick signaling and parent responding can be stable if solicitation is a costly signal. The marginal cost of producing stronger signals allows the system to converge to an equilibrium: young beg with intensity that reflects their need, and parents use this information to maximize their own inclusive fitness. However, we show that there is another equilibrium where chicks do not beg and parents’ provisioning effort is optimal with respect to the statistically probable distribution of chicks’ states. Expected fitness for parents and offspring at the nonsignaling equilibrium is higher than at the signaling equilibrium. Because nonsignaling is stable and it is likely to be the ancestral condition, we would like to know how natural systems evolved from nonsignaling to signaling. We suggest that begging may have evolved through direct sibling fighting before the establishment of a parental response, that is, that nonsignaling squabbling leads to signaling. In multiple-offspring broods, young following a condition-dependent strategy in the contest for resources provide information about their condition. Parents can use this information even though it is not an adaptation for communication, and evolution will lead the system to the signaling equilibrium. This interpretation implies that signaling evolved in multiple-offspring broods, but given that signaling is evolutionarily stable, it would also be favored in species which secondarily evolved single-chick broods.